Study on the Removal of Odorous Gases from Composting Process using Local Bio-Media of Vietnam - Nguyen Nhat Huy; Nguyen Thi Thuy; Lam Pham Thanh Hien; Nguyen Thi Thanh Hang; Vuong Bao Khuong; Le Thi Kim Phung; Nguyen Thi Le Lien (Department of Chemical Engineering, Universitas Gadjah Mada, 2020)
Odor pollution is an increasing problem in Vietnam as a tropical country during the urbanization and industrialization. The odor from sewage systems, farms of poultry, pig, and beef, food processing companies, composting factory, and landfills is a severe problem in many nearby residential areas. In this study, two lab-scale biofiltration systems where pristine local bio-media and cultured bio-media with specially formulated microorganisms were employed in biofilters and bio-trickling filter for controls of odor (i.e., hydrogen sulfide and ammonia) from composting process were fabricated and operated. The odorous gas flow was created by composting solid waste collected from an agricultural market (i.e., mainly vegetable), containing low concentrations of 1.32 ± 0.32 mgNH3 m-3 and 5.20 ± 0.28 mgH2S m-3 under stable condition. For the biofilter model, commercial compost and cow manure were used as substrates and packed into the models. For the bio-trickling filter model, K3 bio-media with biofilm developed by contacting activated sludge was used as packing material. The results showed that adding specially formulated microorganisms could reduce adaption time and lead to slightly better odor control performance. Among the substrates, cow manure provided the highest odorous gas removal efficiency of ≥ 90% during the stable phase with the elimination capacity of 0.0492 gNH3 m-3 h-1 and 0.225 gH2S m-3 h-1. The study results show a high potential of cow manure biofilter for control of H2S and NH3 gases in the practical application under Vietnam’s condition.